Reward Devaluation in Autistic Children and Adolescents with Complex Needs: A Feasibility Study. Issue 11 (10th September 2020) - Lambrechts, Anna; Cook, Jennifer; Ludvig, Elliot A.; Alonso, Eduardo; Anns, Sophie; Taylor, Maddison; Gaigg, Sebastian B.
Abstract : Rewards act as a motivator for positive behavior and learning. Although compounding evidence indicates that reward processing operates differently in autistic individuals who do not have co‐occurring learning disabilities, little is known about individuals who have such difficulties or other complex needs. This study aimed first to assess the feasibility of using an adapted reward devaluation paradigm to examine basic reward processes in this underrepresented population, and second to investigate whether autistic children and adolescents with complex needs would show dynamic behavioral changes in response to changes in the motivational value of a reward. Twenty‐seven autistic children and adolescents with complex needs and 20 typically developing 5‐year‐old children took part in the study. Participants were presented with two visual cues on a touchscreen laptop, which triggered the delivery of a video, music, or physical reward. One of the rewards was then presented in abundance to decrease its motivational value. Participants showed decreased interest in the video and music rewards after devaluation. The experimental setup was found to be suitable to test individuals with complex needs, although recommendations are made for the use of physical rewards. The results suggest that autistic participants with complex needs demonstrate goal‐directed behavior and that it is feasible to develop experimental paradigms that can shed important light on learning processes that are fundamental to many education and intervention strategies for this population. Autism Res 2020, 13 : 1915‐1928. © 2020 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC. Lay Summary: We adapted an experimental task to conduct research with autistic children and adolescents with complex needs, who remain grossly underrepresented in autism research. We found that once a reward was presented in great quantity, participants were less motivated to obtain it, showing that they adapted their behavior to changes in the value of that reward. This is an important finding to help promote learning and design better interventions for this population.